Genital and urinary tract malformations, associated morbidity, and need for urogenital surgery among children with esophageal atresia : a retrospective cohort study - Svensson, Emma ; 0000-0002-4267-3276; Eriksson, Freja; Hagander, Lars ; 0000-0001-6407-4613; Omling, Erik ; 0000-0003-0426-9819; Ellebæk, Mark Bremholm; Salö, Martin (Pediatric Surgery International, 2026)
Purpose: Genital malformations are increasingly recognized when a VACTERL is present, but remain insufficiently described in children with esophageal atresia (EA). This study aimed to determine the prevalence and spectrum of genital and urinary tract malformations in children with EA, and to describe associated morbidity, need for additional surgery, and association with Gross classification. Methods: Retrospective cohort study including all children undergoing surgery for EA at a tertiary center of pediatric surgery between 2012–2023. Children deceased within five days of birth were excluded. Data were collected from medical records and analyzed using Chi2 and Fisher’s exact tests. Results: Ninety-three children were included. Genital and urinary tract malformations occurred in 12 (12.9%) and 18 (19.4%) children. In children with a VACTERL association, the prevalence was 29% (9/31) and 51.6% (16/31), respectively. Urinary tract infections, neurogenic bladder, and intermittent catheterization were more common in children with a genital or urinary tract malformation. Additional urogenital surgery was required in 50% of affected children. There was no significant association with Gross classification. Conclusion: Genital and urinary tract malformations are common in EA, contributing to morbidity and need for additional surgery. Screening for genital malformations should be considered, especially when a VACTERL association is present.
Publisher Copyright: © The Author(s) 2026.
Keywords: CAKUT; Esophageal atresia; Genital malformation; Kidney failure; Urinary tract malformation; VACTERL